2009
DOI: 10.1038/sj.bjc.6604916
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors in shared decision making: a randomised controlled trial in women with a strong suspicion of breast cancer

Abstract: Decision aids in North American breast cancer outpatients have been shown to assist with treatment decision making and reduce decisional conflict. To date, appropriate delivery formats to effectively increase patient participation in newly diagnosed breast cancer inpatients have not been investigated in the context of German health care provision. The impact of a decision aid intervention was studied in patients (n ¼ 111) with a strong suspicion of breast cancer in a randomised controlled trial. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 30 publications
4
86
0
3
Order By: Relevance
“…Notably, the trial that did not report any improved outcomes with decision coaching compared with usual care did not provide values clarification. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the trial that did not report any improved outcomes with decision coaching compared with usual care did not provide values clarification. 21 …”
Section: Discussionmentioning
confidence: 99%
“…21 There was no difference in decisional conflict. 21 Secondary outcomes. Four trials measured choice and 1 trial measured mean costs and physical limitations.…”
Section: Coaching Plus Ptda Versus Usual Care (Four Trials)mentioning
confidence: 97%
See 1 more Smart Citation
“…All showed an increase in patient knowledge and an increase in the use of BCT compared with mastectomy. [4][5][6][7] However, these trials were conducted more than a decade ago and did not address CPM. In the current study by Rosenberg et al, when patients stated that the decision was made by ''patient and doctor together,'' there was a nearly equal distribution of all three surgical procedures.…”
Section: 2mentioning
confidence: 99%
“…This issue has also been reported by Holmes-Rovner et al [21] who investigated barriers and opportunities for implementing shared decision-making in US hospitals, suggesting that this is not unique to Germany. Vodermaier et al [22] pointed out paternalistic physician attitudes and a highly hierarchical health care system as barriers for SDM implementation in the German oncology sector. They investigated the use of a German breast cancer decision aid within a randomized controlled trial and revealed only a small effect on the patients' subjective level of information.…”
Section: Discussionmentioning
confidence: 99%